Apoptosis inhibitor 5 increases metastasis via Erk-mediated MMP expression - Song, Kwon-Ho (BMB Rep, 2015)
Apoptosis inhibitor 5 (API5) has recently been identified as a tumor metastasis-regulating gene in cervical cancer cells. However, the precise mechanism of action for API5 is poorly understood. Here, we show that API5 increases the metastatic capacity of cervical cancer cells in vitro and in vivo via up-regulation of MMP-9. Interestingly, API5-mediated metastasis was strongly dependent on the Erk signaling pathway. Conversely, knock-down of API5 via siRNA technology decreased the level of phospho-Erk, the activity of the MMPs, in vitro invasion, and in vivo pulmonary metastasis. Moreover, the Erk-mediated metastatic action was abolished by the mutation of leucine into arginine within the heptad leucine repeat region, which affects protein-protein interactions. Thus, API5 increases the metastatic capacity of tumor cells by up-regulating MMP levels via activation of the Erk signaling pathway. [BMB Reports 2015; 48(6): 330-335]